2021
DOI: 10.1038/s41575-021-00477-7
|View full text |Cite
|
Sign up to set email alerts
|

Defining comprehensive models of care for NAFLD

Abstract: Nonalcoholic fatty liver disease (NAFLD) is now the leading cause of chronic liver disease globally.Despite the increased demand placed on healthcare systems, little attention has been given to the 2 design and implementation of efficient and effective models of care for patients with NAFLD. In many healthcare settings, no formal pathways exist and where pathways are in place, they are often not standardized according to good practices. We systematically searched the peer-reviewed literature with the aim of id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
238
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 160 publications
(248 citation statements)
references
References 97 publications
8
238
0
2
Order By: Relevance
“…However, most countries, including Western countries, are not prepared to address NAFLD, lacking adequate policies and civil society awareness and engagement, guidelines, epidemiology, and care management [7]. Structural changes and new models of care are needed in order to improve NAFLD management and public health policies [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, most countries, including Western countries, are not prepared to address NAFLD, lacking adequate policies and civil society awareness and engagement, guidelines, epidemiology, and care management [7]. Structural changes and new models of care are needed in order to improve NAFLD management and public health policies [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It is also noteworthy that differentiation and integration of care across primary and secondary care, relating to screening and referral, as well as long-term monitoring, is currently lacking in the guidelines reviewed here. This is reflected in clinical practice, where care pathways are often lacking or, where they do exist, are not standardized based on best-practice principles [46]. The paucity of easy-tofollow care pathways developed from evidence-based best practice therefore remains a major hurdle to translating the knowledge base for NAFLD and NASH into improved outcomes for patients.…”
Section: Algorithms In Guidelinesmentioning
confidence: 99%
“…For example, applying local processes such as the UK's Camden and Islington NAFLD Pathway can reduce unnecessary referrals to specialist care by 80%, offering both clinical and economic efficiencies [73,74]. However, there are currently widespread deficiencies in the number and standardization of care pathways for NAFLD [46]. Specifically, regarding fibrosis evaluation, the available data indicated that assessment of fibrosis using noninvasive techniques is not consistently conducted according to guidelinedefined recommendations, and many physicians are unsure of the assessments and interpretations required or do not apply them rigorously [65,67,75].…”
Section: Discrepancies Between Routine Diagnosis and Screening Practice And The Implementation Of Recommendations In Nafld Guidelinesmentioning
confidence: 99%
“…Despite the rising prevalence and severity of NAFLD, there is still much room for improvement among health care professionals across the lines of care and also on the national guideline level. 21 Lazarus et al 1 conducted a research including 29 European countries for assessment of their NAFLD guidelines and strategies. The United Kingdom scored highest mainly driven by a national guideline that focuses on early detection of NAFLD and associated comorbidities in primary care.…”
Section: Development and Implementation Of Clinical Care Paths And Guidelines For Nafldmentioning
confidence: 99%